The Influence of Online Promotion, Service Quality, and Price on The Sustainability of Culinary Msmes In Parepare City After The Covid-19 Pandemic In The Perspective of Maslahah - Fitriani Fitriani; St. Nurhayati; Muzdalifah Muhammadun; Syahriah Semaun; Andi Bahri S (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Abstract The purpose of this study is to determine the effect of online promotion, service quality, and price on the sustainability of culinary MSMEs in the city of Parepare after the COVID-19 pandemic in the perspective of the community. This type of research is a mixed method. The approach used is a descriptive and associative approach. The research was conducted in Parepare City to MSME actors. Data collection techniques and instruments were carried out through the distribution of questionnaires to 50 samples. The methods used to test the hypothesis are by using pearson product moment correlation analysis techniques, multiple linear regression, f test, coefficient of determination (R2) and interview. The results showed; 1) Online promotion (X1) is very good, evidenced by respondents' answer scores of 88% in the category of 84.01% - 100% with a very good classification. 2) Service quality (X2) is good, evidenced by respondents' answer scores of 83% in the category of 68.01% - 84.00% with a good classification. 3) The price adjustment (X3) is very good, evidenced by the respondent's answer score of 85% in the category of 84.01% - 100% with a very good classification. 4) Sustainability (Y) is very good, evidenced by respondents' answer scores of 85% in the category of 84.01% - 100% with a very good classification. 5) There is no relationship between online promotion (X1) and weak significance to the sustainability variable (Y), evidenced by significance values of 0.088 > 0.05, so there is no correlation. 6) There is no relationship between service quality (X2) and weak significance to the sustainability variable (Y), evidenced by a significance value of 0.122 > 0.05, so there is no correlation. 7) There is no relationship between price (X3) and weak significance to the variable sustainability (Y) as evidenced by a significance value of 0.129> 0.05. 8) Online promotion (X1), service quality (X2), and pricing (X3) have no partial effect on sustainability (Y), as evidenced by their respective significance values of 0.140, 0.229, 0.211 > 0.05, concluded to have no effect. 9) Online promotion (X1), service quality (X2), and price (X3) simultaneously have no significant effect on sustainability (Y), evidenced by a sig of 0.097> 0.05 or a calculated F value of 2.234 < Ftable 2.81 is concluded to have no effect. (10) The most dominant variable for sustainability (Y) is online promotion (X1) with an unstandardized coefficients value of 0.244.( 11) MSME actors in Parepare City maintain the sustainability of their business by implementing good strategies in accordance with the principles of Hajiyyah benefit.